Peran MGMP dalam Meningkatkan Kompetensi Profesional Guru - Riky Syaputra (Journal Islamic Education, 2025)
Teacher professional competence is a crucial factor in supporting the success of the learning process. The MGMP serves as a forum for discussion, pedagogical skill enhancement, and ongoing professional development for teachers. This study employed a qualitative approach with data collection techniques including in-depth interviews, observation, and documentation studies. The results indicate that the MGMP significantly contributes to improving teacher competence through training programs, collaborative learning, and evaluation of learning practices. Furthermore, challenges in implementing the MGMP program were identified, such as limited time and resources. This study recommends strengthening institutional support to optimize the MGMP's role in enhancing teacher professionalism in Islamic boarding schools. This study employed a qualitative approach with a case study method. Data were collected through in-depth interviews with teachers and MGMP administrators, observations of MGMP activities, and analysis of related documents. The results indicate that the MGMP significantly contributes to improving teacher professional competence through various programs, such as training and workshops, focus group discussions, and the development of learning materials. Teachers involved in MGMP activities demonstrated improved abilities in developing Lesson Implementation Plans (RPP), implementing innovative learning methods, and effectively evaluating student learning outcomes. This study provides insight into the important role of MGMP in improving the professional quality of teachers in Islamic boarding school-based educational institutions. These findings are expected to serve as a basis for policy-making and program development that supports teacher competency improvement, particularly in Islamic high schools and Islamic boarding school environments.